Síntese, caracterização e investigação da atividade SERS de nanopartículas de metais não-convencionais - Machado, Thiago Neves (2021)
In this work, we present experimental results on the synthesis and characterization of post-transition metal nanoparticles (antimony, bismuth, lead, tin, and indium). Nanoparticles were synthesized via LASiS (Laser Ablation Synthesis in Solution) by irradiating metallic targets immersed in ultrapure water. The nanoparticles were characterized, as to their shape and size, by Dynamic Light Scattering (DLS) and Transmission Electron Microscopy (TEM). TEM and DLS results indicate that the nanoparticles have size distributions ranging from 5 nm to 100 nm and possess various shapes and formats, being mainly spheres, but also showing other faceted geometries. The nanoparticles were further characterized as to their structural formation by Electron Diffraction in Selected Area (SAED), and the crystalline planes were identified and compared with the literature. The colloidal suspensions were also characterized by UV-Vis optical absorption, showing plasmon resonances mainly in the ultraviolet region and the visible region, indicating the presence of plasmonic activity. The synthesized nanoparticles were used in Raman scattering experiments with diverse analytes: molecules of biological interest such as amino acids (cysteine, glycine, glutamine, methionine, proline, tyrosine, and tryptophan), urea, ascorbic acid, morphine, in addition to a luminescent complex of europium. The results of analyte interrogation with the addition of nanoparticles demonstrate Raman Scattering Signal enhancement, SERS (Surface Enhanced Raman Scattering). It was also shown that the SERS signal enhancement factors of these nanoparticles are comparable to those associated with gold nanoparticles, widely used in SERS applications. Thus, we demonstrate the potential for using these non-conventional metal nanoparticles in SERS detection and characterization for biological materials, particularly SERS-based biosensors.